Linkage QTL Mapping and Genome-Wide Association Study on Resistance in Chickpea to Pythium ultimum - Agarwal, Chiti; Chen, Weidong; Varshney, Rajeev Kumar; Vandemark, George (Frontiers in Genetics, 2022)
The soilborne Oomycete plant pathogen Pythium ultimum causes seed rot and pre-emergence damping-off of chickpea (Cicer arietinum L.). The pathogen has been controlled for several decades using the fungicide metalaxyl as a seed treatment but has re-emerged as a severe problem with the detection of metalaxyl-resistant isolates of the pathogen from infested fields in the USA Pacific Northwest. The objective of this study was to identify genetic markers and candidate genes associated with resistance to P. ultimum in an interspecific recombinant inbred line population (CRIL-7) derived from a cross between C. reticulatum (PI599072) x C. arietinum (FLIP 84-92C) and conduct genome-wide association studies (GWAS) for disease resistance using a chickpea diversity panel consisting of 184 accessions. CRIL-7 was examined using 1029 SNP markers spanning eight linkage groups. A major QTL, “q4-1”, was detected on LG 4 that explained 41.8 % of phenotypic variance, and a minor QTL, “q8-1”, was detected on LG8 that explained 4.5% of phenotypic variance. Seven candidate genes were also detected using composite interval mapping including several genes previously associated with disease resistance in other crop species. A total of 302,902 single nucleotide polymorphic (SNP) markers were used to determine population structure and Kinship of the diversity panel. Marker-trait associations were established by employing different combinations of principal components (PC) and kinships (K) in the FarmCPU model. GWAS detected 11 significant SNPs and 7 candidate genes associated with disease resistance. SNP Ca4_1765418, detected by GWAS on chromosome 4, was located within QTL q4-1 that was revealed in the interspecific CRIL 7 population. The present study provides tools to enable MAS for resistance to P. ultimum and identified genomic domains and candidate genes involved in the resistance of chickpea to soilborne diseases.